Multi-channel broadcast protocol for CRSN based on home channel - Jian-jie PU; Fan-zi ZENG (Tongxin xuebao)
In the light of the limited resources and the dynamic pectrum distribution in the CRSN, a half duplex mul-ti-channel broadcast protocol for CRSN was proposed based on the home channel theory. In the absence of the common channel and clock synchronization, the proposed protoc initialized the network through the transitions of the sending and receiving state of the single transceiver and the nges of the channel table. After network initialization, the to-pology of nodes was formed based on home channel. Nodes broadcast through home channel based on half duplex data transfer mode. According to the simulation results, it is proved that, compared with complete broadcast, the proposed protocol effectively improves the success rate of broadcast and reduces broadcast delay and overhead, which gets better performance in practical application of CRSN.